A systematic review of functional outcomes after nerve reconstruction in extremity soft tissue sarcomas: A need for general implementation in the armamentarium. Issue 4 (April 2020) - Martin, Enrico; Dullaart, Max J.; Verhoef, Cornelis; Coert, J. Henk
Summary: Resection of nerves in extremity soft tissue sarcomas (STS) can lead to large functional deficits. Nerve reconstructions are rarely performed and little is known on their outcomes and indications for their use, even though they are essential in restoring sensation in limb salvage procedures. This study investigated current knowledge on functional outcomes and considerations to be taken before performing such reconstructions after sarcoma resection. A systematic search was performed in July 2018 in PubMed and Embase databases according to PRISMA guidelines. Search terms related to "soft tissue sarcoma" and "nerve reconstruction" were used. Studies evaluating functional outcomes after nerve grafting or nerve transfers in extremity STS were included. Qualitative synthesis was performed on all studies. Nineteen studies were included after full-text screening, describing 26 patients. The majority of patients had a nerve reconstruction in the upper extremity (65%). Perioperative radiotherapy was administered in 67% and perioperative chemotherapy in 29% of patients. Nerve grafting was most commonly performed ( n = 23) and nerve transfers were performed in six patients. A wide variety of outcome measures were used. Most patients recovered at least some motor function and sensation, but success rates were higher after upper than lower extremity defects. Multimodal treatment did not preclude successful reconstructions. Nerve reconstructions in extremity STS allow the restoration of sensation in limb salvation, even motor nerve function can be restored with satisfactory function. The use of multimodal therapy does not seem to interfere with success. Nerve reconstructions should therefore be considered in STS patients.